Research Paper: Transient Absorption Spectroscopy of Deionized Water by Ti: sapphire Femtosecond Laser Pulses - Fereshteh Hajiesmaeilbaigi; Hosein Razzaghi; Eftekhar Sadat Bostandoost; Asama Sadat Motamedi (فیزیک کاربردی ایران)
Transient absorption spectroscopy allows the observation of excited state dynamics following optical excitation across a wide range of time scales, from femtoseconds to milliseconds. This article presents an ultrafast transient absorption spectroscopy setup based on the pump-probe method, utilizing femtosecond pulses from a Ti:sapphire laser at both fundamental and second harmonic wavelengths. We investigated the transient absorption spectrum of deionized water, the most common solvent, with femtosecond time resolution in two modes: one with a fixed delay time for probe wavelengths ranging from 740 to 820 nm, and the other with a fixed probe wavelength for various time delays up to 1.1 picoseconds. The transient absorption spectra reveal a negative signal peaking at 788 nm, attributed to ground state bleaching caused by the depopulation of the ground state induced by the pump. Additionally, a negative signal at 798 nm, resulting from stimulated emission, overlaps with a 10 nm Stokes shift of the ground state bleaching band. The temporal evolution of the transient absorbance spectra shows an absorption peak at a 70 femtosecond delay between the pump and probe pulses, indicating an unstable intermediate level resulting from a two-photon absorption process—one photon from the pump pulse at 392 nm and another from the probe pulse at 784 nm. Fitting a biexponential function to the relaxation data yields a lifetime of approximately 150 femtoseconds for this intermediate leve.